Food adulterations. - Washington, Rebecca Rees (My University, 1905)
Introduction: The question of food adulterations is of very great importance at the present time, since the greater amount of our food supply consists of canned and preserved products. Not many years ago, canned food products were considered luxuries, and only people of means could afford them, but as times have grovel better, there is a growing demand, by all classes of people, for the manufactured goods, and it id the producer trying to meet the popular demand that has, in c great measure, facilitated the manufacture of goods which must necessarily be inferior. The average individual wants the greatest quantity for the least money, regardless of the purity of the article purchased. Manufacturers cannot give high grade food for low prices. Hence the pure product is imitated by using cheap, undesirable, and often poisonous, substances, to give the desired flavor and color. This brings to mind an instance under my own observation. A woman was purchasing baking powder. The clerk showed her several of the better brands and gave prices. She remarked that she wanted something cheaper and when shown the ten cent can, she took it. The law of the state of New York defines adulterations of food as follows: The term food shall include every article of food and drink used and adulterations are (1) If any substance or substances has or have been mixed with it so as to reduce or lower, or injuriously affect, its quality or strength. (2) If any inferior or cheaper substance or substances have been substituted, wholly or in part, for the article. (3) If any valuable material has been wholly or in part abstracted.
Citation: Washington, Rebecca Rees. Food adulterations.. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Food Adulterations in Canned Fruits and Vegetables; Metallic Compounds; Formalin; Theses